From metropolis to metropolis-based region: the case of Tel-Aviv - Raphael Bar-El; John B. Parr (European Regional Science Association (ERSA), 2002)
The decreasing importance of metropolitan areas in the distribution of population and economic activity within many nations of the developed world raises questions about the emergence of agglomeration diseconomies and about the changes in urban spatial structure. Here we explore the thesis that an emerging metropolitan area based region (MBR), comprising the metropolis and a surrounding territory, is gradually replacing the metropolis. Using data covering the last 22 years for the metropolis of Tel-Aviv (Israel) and its surrounding territory, various indicators are estimated. These include national and regional deconcentration (both measured in terms of population and employment), as well as centrality, dependence, attractiveness and integration (measured in terms of employment). The main results of the analysis include the following: the need to view metropolitan stagnation and deconcentration within the wider context of the MBR; employment deconcentration occurring at a slower rate than population deconcentration, leading to increasing levels of employment centrality within the MBR; the process of consolidation within the MBR and a strengthening of its economic role within the nation.
Keywords: 330